Impaired mental well-being and psychosocial risk: a cross-sectional study in female nursing home direct staff. Issue 3 (31st March 2015) - Pélissier, C; Fontana, L; Fort, E; Vohito, M; Sellier, B; Perrier, C; Glerant, V; Couprie, F; Agard, J P; Charbotel, B
Abstract : Objectives: The present study sought to quantify the impaired mental well-being and psychosocial stress experienced by nursing home staff and to determine the relationship between impaired mental well-being assessed on the 12-item General Health Questionnaire (GHQ-12) and exposure to psychosocial stress assessed on Siegrist's effort/reward and overcommitment model. Methods: A transverse study was conducted in France on 2471 female employees in 105 nursing homes for the elderly. Personal and occupational data were collected by questionnaire for 668 housekeepers, 1454 nursing assistants and 349 nurses. Results: 36.8% of participants (n=896) showed impaired mental well-being, 42.7% (n=1039) overcommitment and 9% (n=224) effort/reward imbalance. Overcommitment (prevalence ratio (PR)=1.27; 95% CI (1.21 to 1.34)) and effort–reward imbalance (PR=1.19; 95% CI (1.12 to 1.27)) were significantly associated with presence of impaired mental well-being after adjustment for personal factors (age and private life events). Taking effort and reward levels into account, the frequency of impaired mental well-being was highest in case of exposure to great extrinsic effort and low rewards of any type: esteem, PR=3.53, 95% CI (3.06 to 4.08); earnings, PR=3.48, 95% CI (2.99 to 4.06); or job security, PR=3.30, 95% CI (2.88 to 3.78). Participants in situations of overcommitment and of effort/reward imbalance were at the highest risk of impaired mental well-being: PR=3.86, 95% CI (3.42 to 4.35). Conclusions: Several changes in nursing home organisation can be suggested to reduce staff exposure to factors of psychosocial stress. Qualitative studies of the relation between impaired mental well-being and psychosocial stress in nursing home staff could guide prevention of impaired mental well-being at work.